Occurrence of species of three families, Eulepethidae, Apistobranchidae, and Heterospionidae (Polychaeta) from Japan - Imajima, Minoru (Bulletin of the National Science Museum, Tokyo, 1974)
None. Begins: "The three polychaete families Eulepethidae, Apistobranchidae and Heterospionidae are all small, known for only few species, and have not been previously reported from Japanese waters. This study is based on material from three sources: Eulepethidae from Miho Bay, Tottori Prefecture, in 30 m, collected by the member of the Shimonoseki University of Fisheries; Apistobranchidae from off Samani, Hokkaido, in 60 m, collected by the author; Heterospionidae from Suruga Bay, in 300- 450 m, collected by the survey in Tansei Maru Cruise KT-68-2. In the present study a new genus and a new species of the Eulepethidae is proposed. "
World Polychaeta Database (WPolyDb)